Concussion risk and the need for prevention: an exploration into the complexity of community perspectives in rugby union - Badenhorst, M.; Romanchuk, J.; Salmon, D.; Brown, J. C.; Hendricks, S.; Walters, S. (Sports Medicine, 2025)
Background: Community perceptions of injury risk can impact participation rates and may influence attitudes and behaviours around prevention efforts. Understanding how end-users think about concussion-related risk and the need for prevention is critical for the design and implementation of interventions. This study aimed to explore community rugby union stakeholders` perceptions of concussion risk and the need for prevention. Methods: This pragmatic, qualitative descriptive study utilised semi-structured interviews and focus groups with 62 school- and club-level community rugby stakeholders (provincial union representatives, players, coaches, school/club sport administrators, team leads (managers), physiotherapists, nurses and doctors) from across New Zealand during the 2022 rugby season. Reflexive thematic analysis was used to analyse the data. Results: Three themes were developed from the data. The theme `concussion risk: a spectrum of concern` included a spectrum of beliefs ranging from `concussions are a problem` to the belief that concussions are only a problem if not managed well or that it has always been part of the game, and the risks are being exaggerated. A second theme, `focus on technique and conditioning, or is injury just the nature of the game?`, described beliefs in the importance of technique and conditioning or contrary beliefs such as `as long as there is contact, there will be concussion`. A third theme, `conflicting concussion narratives`, described the tendency of some participants to move back and forth across the spectrum of risk and prevention perceptions, depending on the context. Conclusions: Findings reveal a diversity of perspectives on how concussions should be managed or prevented. Balancing these perspectives is critical. This involves addressing unfavourable beliefs, prioritizing both prevention and effective management and community-wide education.